2022
DOI: 10.3390/children9091289
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Silver Diamine Fluoride in Arresting Caries in Primary and Early Mixed Dentition: A Systematic Review

Abstract: Dental caries is a painful condition that could lead to nutritional problems which affects the overall health of the child, as well it is expensive to treat. The effectiveness of silver diamine fluoride (SDF) in primary and early mixed dentition is systematically reviewed in this study. This systematic review utilized the Preferred Reporting Items for Systematic reviews and Meta- Analysis statement (PRISMA, 2020). A literature search conducted using the common electronic databases (from 2010–2021). Based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
1
0
Order By: Relevance
“…One study has shown a reduction of the new active lesion percentage in both primary and permanent teeth following the application of 38% SDF [ 7 ]. Furthermore, a systematic review has proven the efficacy of 38% SDF on both primary and permanent molars with a higher cariostatic success when compared to different topical fluoride products [ 12 ]. However, some suggested further research to confirm its equal results on permanent molars [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One study has shown a reduction of the new active lesion percentage in both primary and permanent teeth following the application of 38% SDF [ 7 ]. Furthermore, a systematic review has proven the efficacy of 38% SDF on both primary and permanent molars with a higher cariostatic success when compared to different topical fluoride products [ 12 ]. However, some suggested further research to confirm its equal results on permanent molars [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Silver diamine fluoride (SDF) proved to be a successful, non-invasive, and cost-effective tool in arresting caries [11][12][13][14]. In addition, it proved to be a useful option when treatment under general anesthesia is not feasible [11].…”
Section: Discussionmentioning
confidence: 99%
“…As for deciduous teeth, SDF has been shown in numerous studies to prevent and arrest deep carious lesions in high caries risk children [86][87][88][89] [44,47]. Zaffarano et al concluded in the same idea in comparison with ART and fluoride in his review [91].…”
Section: % Sdfmentioning
confidence: 99%
“…Many of these materials, such as fluoride varnishes, contain fluoride. Fluoride (F) is expected to improve the acid resistance of enamel and dentin and to promote remineralization [ 6 , 7 , 8 , 9 , 10 , 11 ]. It is widely used for caries prevention and its effectiveness is well established.…”
Section: Introductionmentioning
confidence: 99%